2015
DOI: 10.1371/journal.pone.0142095
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Kinetics of Agitation-Induced Aggregation of Hen Lysozyme under Heat and Acidic Conditions from Various Spectroscopic Methods

Abstract: Protein misfolding and amyloid formation are an underlying pathological hallmark in a number of prevalent diseases of protein aggregation ranging from Alzheimer’s and Parkinson’s diseases to systemic lysozyme amyloidosis. In this context, we have used complementary spectroscopic methods to undertake a systematic study of the self-assembly of hen egg-white lysozyme under agitation during a prolonged heating in acidic pH. The kinetics of lysozyme aggregation, monitored by Thioflavin T fluorescence, dynamic light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 90 publications
(182 reference statements)
3
42
0
Order By: Relevance
“…During the fibrillation of lysozyme, an increase in b-sheet content occurs gradually, as highlighted by CD as well as IR studies. The increase in b-sheet content is consistent with previous results on lysozyme by other groups (Chaari, Fahy, Chevillot-Biraud, & Rholam, 2015;Frare et al, 2009;Malisauskas et al, 2003) and indicates the common feature during amyloid fibrillation.…”
Section: Discussionsupporting
confidence: 91%
“…During the fibrillation of lysozyme, an increase in b-sheet content occurs gradually, as highlighted by CD as well as IR studies. The increase in b-sheet content is consistent with previous results on lysozyme by other groups (Chaari, Fahy, Chevillot-Biraud, & Rholam, 2015;Frare et al, 2009;Malisauskas et al, 2003) and indicates the common feature during amyloid fibrillation.…”
Section: Discussionsupporting
confidence: 91%
“…Ultrasonic treatment (UST) is often used for preparation of fibril seeds in studies of amyloid aggregation. It breaks fibrils into shorter pieces [7] increasing the number of fibril ends that act as active aggregation sites and accelerating elongation rate without a change of total protein concentration. Fragments of fibrils were obtained via sonication of mature fibril samples.…”
Section: Methodsmentioning
confidence: 99%
“…Systemic amyloidosis is a lysozyme-associated disease caused by the deposition of lysozyme in the amyloid fibril form in spleen, kidney, and liver cells [ 33 , 36 ]. Previous studies have shown that lysozyme can easily form amyloid fibrils under different conditions, such as high temperatures and appropriate pH conditions [ 37 40 ]. Many amyloidogenic proteins interact with the surfaces of basement membranes; SDS has the potential to mimic this condition [ 29 , 41 45 ].…”
Section: Introductionmentioning
confidence: 99%